2017
DOI: 10.1139/cgj-2017-0209
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of vane shear tests for geotechnical stability calculations

Abstract: In this note we consider the problem of calibrating failure criteria for short-term stability calculations based on the results of vane shear tests. Numerical and theoretical considerations supported by experimental data provide evidence that we can use the vane shear test to obtain the undrained strength of a sample tested under simple shear conditions at a normal stress equal to the horizontal effective stress at the given depth. Consequently, it is argued that there is no need to correct the field vane undr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Laboratory tests reported by Pineda et al (2016a), obtained from tube samples retrieved using the O89 sampler, provided specimens of 'excellent' and 'good' quality. provide similar values to those obtained from simple shear tests (e.g., Terzaghi et al 1996;Kouretzis et al 2017), are also reported in Figure 18 for comparison. Very good agreement is observed between laboratory values and in situ characterization studies and parameters estimated here for block and O89 samplers.…”
Section: Implications Of Sampling Disturbance In Geotechnical Designsupporting
confidence: 87%
“…Laboratory tests reported by Pineda et al (2016a), obtained from tube samples retrieved using the O89 sampler, provided specimens of 'excellent' and 'good' quality. provide similar values to those obtained from simple shear tests (e.g., Terzaghi et al 1996;Kouretzis et al 2017), are also reported in Figure 18 for comparison. Very good agreement is observed between laboratory values and in situ characterization studies and parameters estimated here for block and O89 samplers.…”
Section: Implications Of Sampling Disturbance In Geotechnical Designsupporting
confidence: 87%
“…A comparison of the measured undrained shear strength, , in different types of laboratory test is often cited as a measure of the 'strength anisotropy' of the clay; however, this terminology is potentially misleading when used to describe a general stress path dependency. As noted by Kouretzis et al (2017), an isotropic model may exhibit different values for triaxial compression and extension tests due to the yield strength in the deviatoric plane being dependent on Lode angle ( ).…”
Section: Monotonic Behaviourmentioning
confidence: 99%
“…The model does not include the influence of inherent anisotropy and it is recognised that this omission may be significant for some natural clays. However, the model can readily be extended to include the influence of inherent anisotropy by using a modified deviatoric stress tensor to define the yield and plastic potential functions for all of the micro models, following a similar approach to Prevost (1977), Grimstad et al (2012) and Kouretzis et al (2017). In this case, all occurrences of in the definition of the yield surface and plastic potential of each micro model (Section 3.1) are replaced by .…”
Section: Multi-surface Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a vane height-to-diameter ratio of 2 and conventional stress distribution on the cylindrical surfaces, the vertical shear surface contributes 86% of the shear resistance (Chandler, 1988). Furthermore, Kouretzis et al (2017) indicated that vane shear strength is analogous to direct simple shear conditions in the vertical plane with σ h = K 0 •σ v . Therefore, strength conditions in vane shear were best represented as τ p vs. σ h in a conventional Mohr-Coulomb assessment.…”
Section: Shear Strengthmentioning
confidence: 99%